A black finger does not equal a dead finger - Shalimar Abdullah,; William H,; Levin KB,; Parminder GS,; Nur Azuatul AK,; Tan, JA; Ahmed Suparno BM, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Revascularisation and replant surgery occasionally produces sub-optimal results. We present two cases of near total amputation of the digits. The first patient was an 11-year-old boy with a middle finger avulsion injury sustained after the finger was caught in a washing machine with the flexor digitorum profundus still attached. The second patient was a 42-year-old male who sustained a machete attack and had near total amputation of his small and ring fingers with a 2 cm skin bridge still attached. All patients underwent revascularization with repair of only one digital artery for each finger as the opposite artery was non-viable. No digital veins were repaired. Relief of venous congestion was done by pin-prick six times a day up till one week. At one week post-surgery, the fingers were discoloured black but had good pulp turgor and full contour with arterial bleed on pin-prick. Inexperienced surgeons may view this as gangrene and amputate the fingers. However, we continued observation and at one month post-surgery, the black skin had desloughed and the underlying skin was pink.